Simulating the Dynamics of Stock Price via PSO-Assisted Quantum Anharmonic Oscillator Model: Case of Jakarta Composite Index - Tony Sumaryada; Anisah Rahajeng Kartika Sari; Agus Kartono (Universitas Islam Negeri (UIN) Mataram, 2022)
The Jakarta Composite Index (JCI) stock price dynamics have been modeled by a quantum anharmonic oscillator and the PSO (Particle Swarm Optimization) Algorithm. Some of the constants that affect the probability density of return are the ability of the market makers to control the market (γ), the behaviour of contrarians and the trend followers to the price return (c), and the investor behaviour towards perceived volatility (k). The simulation results have produced the slightest error of the JCI at 8.36% for the opportunity density and 3.6% for the stock price returns. Forward prediction for the next three months using the exponential smoothing method resulted in a 17.77% error in the opportunity density of the stock price return and a 10.6% error in the stock price return. Based on those results, it can be concluded that the stock price dynamics can be modelled using an anharmonic quantum oscillator where the value of liquidity and volatility in the previous period affects the investor and the stock's price return in the next period.